An Approach to Childhood Movement Disorders: Review - Bingol, Zeynep A.; Bulut, Serpil (Ortadogu Ad Pres & Publ Co, 2009)
Involuntery movements are generally associated with abnormalities of he basal ganglia and their connections. They occur in different neurological disorders. The role of genetic factors, positive family history, ethnic origin, triggering factors, specific clinical picture and response to treatment are important in diagnosis. Differential diagnosis of epilepsy should be made. Chorea is an irregular, rapid, uncontrolled, repetitive involuntery movement. That is often included into a voluntery movement to hide it. Sydenham chorea is neurological sign of rheumatic fever. However, distinction of Sydenham and lupus chorea is difficult. Athetosis is sometimes seen with chorea (chorea-athetosis). Ballismus is considered as another form of chorea. Infectious, vascular, metabolic/degenerative and paroxismal diseases, benign hereditary chorea, drugs, tumors and psychogenic factors are ethiologic causes of childhood's chorea/ballismus. Appearance, prognosis, accompanying neurological symptom/signs and family history are important in differential diagnosis of ataxia. Posterior fossa lesions, hereditary chronic progresive ataxia, sensorial ataxia, recurrent ataxia, vitamin E responsive ataxia and labyrinthine diseases, spinocerebellar degenerations, Friedreich's ataxia and ataxi-telengiectasia are in diferential diagnosis. Major causes of dystonia include; perinatal asphixia, kern icterus, generalized primary dystonia, drugs, Wilson disease and Hallervarden-Spatz disease and other genetic mutations. Primary generalized dystonia may be duo to a group of genetic disease. Dystonia may be focal, segmental, multifocal, hemidystonia or generalized. Gilles de la Tourette syndrome is a neuropsychiatric disorder characterized by both vocal and motor tics. Affected individuals often display symptoms of attention deficit hyperactivity disorder and obsessive-compulsive disorder. Myoclonus is the contraction of muscle or muscle groups. As well as it may be generalized, essential or focal, it may also occur as a component of progresive myoclonic epilepsy.
Keywords: Childhood; movement disorders